APRENDIZAGEM INVENTIVA NOS CURRÍCULOS ESCOLARES - Rodrigues, Jaconias Dias (2020)
The research presented here is inspired by cartography for the production of data in school curricula under the inspiration of the philosophy of difference. The experiences woven in school daily life, despite the hard lines, there are also escape lines t